Eugene Garfield’s Influences upon the Future of Evaluative Informetrics - Moed, Henk F. (Frontiers in Research Metrics and Analytics, 2018)
This contribution highlights Eugene Garfield’s influences upon the author’s views and proposals. In addition, it presents the author’s perspective on the future of evaluative informetrics, based on his monograph Applied Evaluative Informetrics published in September 2017. It discusses main criticisms against the current practices in the use of informetric indicators in research assessment, and sketches a series alternative approaches.